From: archive Goldman, 22. Dedication on back: 'Wer kommt denn da an? Come slowly towards me! Oui Arri Baby Nice 15.3.31.' (1931)
From: archive Goldman, 22. Dedication on back: 'Wer kommt denn da an? Come slowly towards me! Oui Arri Baby Nice 15.3.31.'.